Anatomical, physiological and allometric contrasts of the Cerrado tree Dalbergia miscolobium in full sun and shade environments. Issue 2 (2nd April 2020) - Mendonça, Ane Marcela das Chagas; Lira, Jean Marcel Sousa; Rodrigues, Marcelo; Monteiro, Vanessa da Fontoura Custódio; Simão, Edson; Barbosa, João Paulo Rodrigues Alves Delfino
Abstract : The Brazilian Cerrado is a mosaic comprised of different vegetation formations and consequently, different environmental conditions. Tree density modifies the availability of light and affects species distribution. Thus, seedlings of species with a broad distribution should show contrasting anatomical, morphological, and physiological traits depending on environmental conditions, and this should account for a higher phenotypic plasticity as part of their survival strategies. Our aim was to investigate the ability of Dalbergia miscolobium, a widespread species in the Cerrado, to modify physiological, allometric, and anatomical traits under full sunlight and shade conditions. In a shade environment, D. miscolobium had increased tree height, number of leaves, chlorophyll content, and specific leaf area; in full sun, nett photosynthesis, stomatal conductance, transpiration, and leaf thickness increased. Also, root-to-shoot ratio (R:S ratio) was ∼70% greater in the full sun than the shade. A high relative distance phenotypic index, which quantifies phenotypic plasticity by the relative distance among the individual traits, was observed for R:S ratio (0.37), indicating the ability of D. miscolobium to change its biomass allocation in different environments. The contrasts in the studied traits under the two light conditions may be related to changes in carbon investment with light availability. This phenotypic plasticity may explain the broad distribution of D. miscolobium .